A Comparative Genomics Study on the Molecular Evolution of Serotonin/Melatonin Biosynthesizing Enzymes in Vertebrates - Lv, Yunyun; Li, Yanping; Li, Jia; Bian, Chao; Qin, Chuanjie; Shi, Qiong (Frontiers in Molecular Biosciences, 2020)
Serotonin is important in vertebrates for its crucial roles in regulation of various physiological functions. Investigations on how the biosynthesizing enzymes mediate serotonin production and conversion during biological processes have been active in the past decades. However, a clear-cut picture of these enzymes in molecular evolution is very limited, particularly when the complexity is imaginable in fishes since teleosts had experienced additional whole genome duplication (WGD) event(s) than tetrapods. Since serotonin is the main intermediate product during melatonin biosynthesis from tryptophan, we therefore summarize an overview of recent discoveries about molecular evolution of the four melatonin biosynthesizing enzymes, especially the L-aromatic amino acid decarboxylase (AAAD) for serotonin production and aralkylamine N-acetyltransferase (AANAT) for serotonin conversion in vertebrates. Novel copies of these genes, possibly due to WGD, were discovered in fishes. Detailed sequence comparisons revealed various variant sites in these newly identified genes, suggesting functional changes from the conventional recognition of these enzymes. These interesting advances will benefit readers to obtain new insights into related genomic differences between mammals and fishes, with an emphasis on the potential specificity for AANAT in naturally cave-restricted and deep-sea fishes.